2022
DOI: 10.3390/coatings12040497
|View full text |Cite
|
Sign up to set email alerts
|

Hot Corrosion Behavior of Arc-Sprayed NiCrB and NiCrTi Coatings with Different Oxide Contents

Abstract: In this study, newly developed NiCrB and conventional NiCrTi coatings were produced by arc spraying using compressed air and nitrogen as atomization gases. In this way, four coatings with different oxide contents were produced. The coatings were investigated in terms of their phase compositions, oxygen contents, and microstructures. The results showed that the oxygen contents in coatings were pronouncedly reduced by nitrogen-atomized compared to air-atomized. The oxygen contents in the nitrogen-atomized coatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
(31 reference statements)
1
1
0
Order By: Relevance
“…Figure 6 displays the EDX elemental mappings of the NiCrTi coating. Detected XRD phases are consistent with those reported by Wang [ 57 ] for the TWAS spray NiCrTi coating in a molten salt environment of 90% Na 2 SO 4 -10% NaCl. The results are found to be also similar to those reported by Guo [ 58 ] for the TWAS sprayed NiCrTi in a molten salt environment of 70% Na 2 SO 4 -30% K 2 SO 4 .…”
Section: Discussionsupporting
confidence: 88%
“…Figure 6 displays the EDX elemental mappings of the NiCrTi coating. Detected XRD phases are consistent with those reported by Wang [ 57 ] for the TWAS spray NiCrTi coating in a molten salt environment of 90% Na 2 SO 4 -10% NaCl. The results are found to be also similar to those reported by Guo [ 58 ] for the TWAS sprayed NiCrTi in a molten salt environment of 70% Na 2 SO 4 -30% K 2 SO 4 .…”
Section: Discussionsupporting
confidence: 88%
“…In a study, Singh et al, 38 revealed that TiO 2 functions as a protective barrier against corroding agents by occupying any gaps or fractures in the coating's microstructure. Wang et al, 39 found that NiCrB coatings have greater corrosion resistance in comparison to NiCrTi coatings as a result of boron's inclination towards producing small oxide particles, ultimately augmenting the safeguarding of oxide layers. Abuwarada et al, 40 showed that the presence of a stable Al 2 O 3 oxide scale on the CoNiCrAlY coating reduced chloride penetration and prevented the degradation of the protective oxide scale through the formation of chromates.…”
Section: Coatings Tested Under Aggressive Environments By Various Res...mentioning
confidence: 99%